VDC_100102371237.0X000001. Issue 10 (October 2018) - Babcock, Blake; Jabo, Brice; Selleck, Matthew; Reeves, Mark; Garberoglio, Carlos; Namm, Jukes; Kazanjian, Kevork; Senthil, Maheswari
Cytoreductive surgery and hyperthermic intraperitoneal chemotherapy (CRS/HIPEC), although considered an acceptable treatment option in the management of selected patients with colon and appendiceal peritoneal carcinomatosis (PC), concerns about morbidity have limited its acceptance. Our objective was to evaluate the short- and long-term outcomes of CRS/HIPEC for appendix and colon PC performed at our institution and to elucidate factors predictive of patient outcomes. All patients who underwent CRS/HIPEC for appendix or colon PC from 2011 to 2017 were identified from our institution's prospective database. Postoperative outcomes, overall survival, and recurrence-free survival were assessed. Of 125 patients who underwent CRS/HIPEC during the study period, 45 patients were eligible (appendix n = 26; colon n = 19). The median postoperative length of stay was nine days (5–28 days). Grade III/IV complications occurred in 4/45 (8.8%) patients. There were no postoperative mortalities. Median DFS and overall survival have not yet been reached, in both the colon and appendix groups. As of the study conclusion date, 37/45 (82.2%) patients were alive with or without disease. Lymph node status was predictive of recurrence in appendix PC. In our experience, CRS/HIPEC can be safely performed with acceptable short- and long-term outcomes. Lymph node status is an important predictor of recurrence.